Open Legal Policy Regarding the Age Limit of Notary Public Based on Constitutional Court Decision Number. 84/PUU-XXII/2024 - Munthe, Gerald Elisa (Rechtsvinding, 2025)
Open legal policy emerged when the 1945 Constitution gave an order to regulate a norm through a law, in this case the Legal Regulation of Article 8 Paragraph (2) of Law Number 2 of 2014 as an amendment to Law Number 30 of 2004 concerning the Position of Notary. The research method used is normative juridical or library research, by analyzing library materials or secondary data relevant to the topic. This research is descriptive analytical, namely the data obtained and processed and analyzed to provide a comprehensive picture of the open legal policy in the norming of Article 8 paragraph (2) which regulates the age limit of the notary office as stated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary. Research Results Show that the determination of the age limit for notaries is part of an open legal policy that is within the authority of the legislators, as long as it does not conflict with the principles guaranteed in the 1945 Constitution. However, this policy can be considered invalid if it violates constitutional principles, such as the principle of non-discrimination, equality before the law, and the feasibility and rationality of public policy.